Linear boundary-value problems described by Drazin invertible operators - Messirdi, Bekkai; Khaldi, Nassima; Benharrat, Mohammed (Mathematical Notes, 2017)
The main subject of this paper is the study of a general linear boundary-value problem with Drazin or right Drazin (respectively, left Drazin) invertible operators corresponding to initial boundary operators. The obtained results are then employed to solve a Schro¨ dinger equation.